Email subject lines in the business context. - Chao, Karen Sin Hui. (2008)
Email subject lines are growing in importance to ensure effective communication. This report focuses on the writing and reading habits of individuals, email management in offices, the impact of spam and how the writing of email subject lines can bring about efficiency to businesses in communication.